Data release: targeted systematic literature search for tick and tick-borne pathogen distributions in six countries in sub-Saharan Africa from 1901 to 2020 - Abigail A. Lilak; David B. Pecor; Graham Matulis; Alexander M. Potter; Rachel N. Wofford; Mary F. Kearney; Stephanie Mitchell; Fatima Jaradat; Arisa Kano; Dawn M. Zimmerman; James M. Hassell; Bersissa Kumsa; et al. (Parasites & Vectors, 2024)
Abstract Background Surveillance data documenting tick and tick-borne disease (TBD) prevalence is needed to develop risk assessments and implement control strategies. Despite extensive research in Africa, there is no standardized, comprehensive review. Methods Here we tackle this knowledge gap, by producing a comprehensive review of research articles on ticks and TBD between 1901 and 2020 in Chad, Djibouti, Ethiopia, Kenya, Tanzania, and Uganda. Over 8356 English language articles were recovered. Our search strategy included 19 related MeSH terms. Articles were reviewed, and 331 met inclusion criteria. Articles containing mappable data were compiled into a standardized data schema, georeferenced, and uploaded to VectorMap. Results Tick and pathogen matrixes were created, providing information on vector distributions and tick–pathogen associations within the six selected African countries. Conclusions These results provide a digital, mappable database of current and historical tick and TBD distributions across six countries in Africa, which can inform specific risk modeling, determine surveillance gaps, and guide future surveillance priorities. Graphical Abstract